2003
DOI: 10.1248/jhs.49.405
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Sodium Spirulan on the Secretion of Fibrinolytic Proteins from Vascular Endothelial Cells: Enhancement of Plasminogen Activator Activity

Abstract: Sodium spirulan (Na-SP) is a sulfated polysaccharide with M r ~220000 isolated from the blue-green alga Spirulina platensis. Na-SP influences the blood coagulation-fibrinolytic system by activation of heparin cofactor II in vitro, although it has been incompletely understood whether the polysaccharide can act on vascular endothelial cell functions. In the present study, we investigated the effects of Na-SP on the fibrinolytic activity of human coronary endothelial cells in a culture system. It was found that N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…The results support the hypothesis that Na-SP enhances the local anticoagulant activity in the liquid phase on the endothelium by two mechanisms: one is direct activation of heparin cofactor II 15,23) and the other is the promotion of the endothelial release of perlecan and biglycan that can activate antithrombin III 10) and heparin cofactor II, 12) respectively. Na-SP may be a beneficial agent for the prevention of atherosclerosis because of these anticoagulant properties of Na-SP, in addition to the enhancement of endothelial fibrinolytic activity 16) and the inhibition of vascular smooth muscle cell proliferation. 39) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results support the hypothesis that Na-SP enhances the local anticoagulant activity in the liquid phase on the endothelium by two mechanisms: one is direct activation of heparin cofactor II 15,23) and the other is the promotion of the endothelial release of perlecan and biglycan that can activate antithrombin III 10) and heparin cofactor II, 12) respectively. Na-SP may be a beneficial agent for the prevention of atherosclerosis because of these anticoagulant properties of Na-SP, in addition to the enhancement of endothelial fibrinolytic activity 16) and the inhibition of vascular smooth muscle cell proliferation. 39) …”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that Na-SP enhances the fibrinolytic activity of the cells through inhibition of plasminogen activator inhibitor-1 secretion. 16) This indicates that Na-SP can modulate the anticoagulant and fibrinolytic properties of vascular endothelial cells. We hypothesized that Na-SP may influence the metabolism of endothelial PGs, since heparin has a stimulatory effect on the release of PGs from vascular endothelial cells.…”
mentioning
confidence: 96%
“…11) In addition, the effects of Na-SP on vascular endothelial cell functions, including inhibition of the proliferation, 24) inhibition of the secretion of plasminogen activator inhibitor type 1 12) and stimulation of the release of proteoglycans, 13) disappear after desulfation. It has been shown that several biological activities of SCA also require the sulfate group.…”
Section: Discussionmentioning
confidence: 99%
“…11) In vascular endothelial cells, Na-SP elevates the fibrinolytic activity of vascular endothelial cells through inhibition of the secretion of plasminogen activator inhibitor type 1. 12) In addition, Na-SP promotes the secretion of anticoagulant proteoglycans 13) such as perlecan and biglycan, 14) as well as exhibiting an antithrombin activity through activation of heparin cofactor II. 15,16) We hypothesized that CA or SCA may inhibits the proliferation of vascular smooth muscle cell proliferation, as does natural or semi-synthetic polysaccharides, including Na-SP, heparin, 17) pentosan polysulfate 18) and fucoidan.…”
mentioning
confidence: 99%
“…4) Na-SP enhances the fibrinolytic activity in the liquid phase of cultured human coronary endothelial cells through inhibition of plasminogen activator inhibitor type 1 secretion. 5) Recent study has shown that Na-SP is a potent inhibitor of cultured vascular smooth muscle cell proliferation. 6) Those results indicate that Na-SP has anticoagulant, fibrinolytic, and antiatherogenic properties in vitro.…”
Section: Introductionmentioning
confidence: 99%